To write the equation of a circle in standard form, you can use the formula:
\[ (x - h)^2 + (y - k)^2 = r^2 \]
where \((h, k)\) is the center of the circle and \(r\) is the radius.
In this case, you are given:
- Center \((h, k) = (5, 0)\)
- Radius \(r = 3\)
Now, substituting these values into the formula, we have:
\[ (x - 5)^2 + (y - 0)^2 = 3^2 \]
This simplifies to:
\[ (x - 5)^2 + y^2 = 9 \]
Now, comparing this with your options, the correct equation for the circle in standard form is:
\[ \left( x - 5 \right)^2 + y^2 = 9 \]
Therefore, the correct response is:
left parenthesis x minus 5 right parenthesis squared plus y squared equals 9